(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Asthma is a common chronic inflammatory disease of the airways characterized by variable and recurring symptoms, reversible airflow obstruction and bronchospasm.[1] Asthma is the result of chronic inflammation of the airways which subsequently results in increased contractability of the surrounding smooth muscles. This among other factors leads to bouts of narrowing of the airway. The narrowing is typically reversible with or without treatment. Occasionally the airways themselves change. Common symptoms include wheezing, coughing, chest tightness.